Protocol for the surgical and large bore procedures in malignant pleural mesothelioma and radiotherapy trial (SMART Trial): an RCT evaluating whether prophylactic radiotherapy reduces the incidence of procedure tract metastases - Clive, Amelia O (BMJ Open, 2015)
INTRODUCTION: Patients with malignant pleural mesothelioma (MPM) may develop painful ‘procedure tract metastasis’ (PTM) at the site of previous pleural interventions. Prophylactic radiotherapy has been used to minimise this complication; however, three small randomised trials have shown conflicting results regarding its effectiveness. The surgical and large bore procedures in malignant pleural mesothelioma and radiotherapy trial (SMART Trial) is a suitably powered, multicentre, randomised controlled trial, designed to evaluate the efficacy of prophylactic radiotherapy within 42 days of pleural instrumentation in preventing the development of PTM in MPM. METHODS AND ANALYSIS: 203 patients with a histocytologically proven diagnosis of MPM, who have undergone a large bore pleural intervention (thoracic surgery, large bore chest drain, indwelling pleural catheter or local anaesthetic thoracoscopy) in the previous 35 days, will be recruited from UK hospitals. Patients will be randomised (1:1) to receive immediate radiotherapy (21 Gy in 3 fractions over 3 working days within 42 days of the pleural intervention) or deferred radiotherapy (21 Gy in 3 fractions over 3 working days given if a PTM develops). Patients will be followed up for 12 months. The primary outcome measure is the rate of PTM until death or 12 months (whichever is sooner), as defined by the presence of a clinically palpable nodule of at least 1 cm diameter felt within 7 cm of the margins of the procedure site as confirmed by two assessors. Secondary outcome measures include chest pain, quality of life, analgaesic requirements, healthcare utilisation and safety (including radiotherapy toxicity). ETHICS AND DISSEMINATION: The trial has received ethical approval from the Southampton B Research Ethics Committee (11/SC/0408). There is a Trial Steering Committee, including independent members and a patient and public representative. The trial results will be published in a peer-reviewed journal and presented at international conferences. TRIAL REGISTRATION NUMBER: ISRCTN72767336.